Integrating the Huma Betang Philosophy into Progressive Islamic Education in Elementary Schools: A Study on Curriculum Development - Salasiah Salasiah; Khairil Anwar (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This study examines integrating the Huma Betang philosophy a way of life rooted in the Dayak community of Central Borneo into the curriculum of progressive Islamic education. The core values of Huma Betang, such as solidarity, collaboration, tolerance, and respect for diversity, align closely with the principles of Islamic education, which emphasize character formation and moral development. This research is motivated by the need to respond to the challenges faced by modern Islamic education, including those related to globalization, pluralism, and technological advancement. A qualitative descriptive method was employed, using a literature review approach through thematic analysis of relevant sources. The findings reveal that integrating Huma Betang values can enhance students' character development, increase social awareness, and foster an inclusive and contextual Islamic identity. Moreover, a curriculum incorporating local values has proven to be more relevant to the socio-cultural realities of the community, thereby improving the effectiveness of education. However, several challenges were identified, such as educators' low awareness of the importance of local wisdom, limited teacher training, and the rigidity of national curriculum regulations. This study recommends strategies such as local value-based teacher training, developing contextual pedagogy, and formulating a flexible curriculum that adapts to local culture. In conclusion, integrating the Huma Betang philosophy into Islamic education in elementary schools enriches the curriculum substantively and significantly contributes to producing graduates who are ethical, socially responsible, and ready to face global challenges without losing their cultural and spiritual roots.